2014
DOI: 10.1136/annrheumdis-2014-eular.3728
|View full text |Cite
|
Sign up to set email alerts
|

OP0227 Oral C5a Receptor Antagonist CCX168 Phase 2 Clinical TRIAL in Anca-Associated Renal Vasculitis:

Abstract: Background In ANCA vasculitis, the anaphylatoxin C5a amplifies neutrophil influx and activation through C5aR. CCX168, an oral specific C5aR antagonist, is in clinical development for ANCA-associated renal vasculitis (AARV). Objectives A Phase 2 clinical trial was conducted to investigate the potential of CCX168 to contribute to disease remission and permit glucocorticoid reduction or avoidance in patients with active AARV receiving cyclophosphamide (CYC). Methods This randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The preliminary results of a small phase II trial evaluating efficacy and safety indicate that CCX168 plus cyclophosphamide is at least as effective, if not more effective, as full dose steroids plus cyclophosphamide in patients with newly diagnosed renal AAV [69]. Since high-dose glucocorticoids are increasingly believed to be the major contributor to early toxicity and infectious adverse events, the possibility of a steroid-sparing agent, with the convenience of oral administration is an extremely exciting development.…”
Section: C5a Inhibitor (Ccx168)mentioning
confidence: 96%
“…The preliminary results of a small phase II trial evaluating efficacy and safety indicate that CCX168 plus cyclophosphamide is at least as effective, if not more effective, as full dose steroids plus cyclophosphamide in patients with newly diagnosed renal AAV [69]. Since high-dose glucocorticoids are increasingly believed to be the major contributor to early toxicity and infectious adverse events, the possibility of a steroid-sparing agent, with the convenience of oral administration is an extremely exciting development.…”
Section: C5a Inhibitor (Ccx168)mentioning
confidence: 96%
“…CYC plus high-dose prednisone tapering. The results showed that CCX168 plus CYC appeared to be at least as effective, if not more effective, as full-dose GC plus CYC in improving renal parameters and inducing remission of renal vasculitis [85]. TCZ was successfully used in a case of a woman with MPO-ANCA pauci-immune glomerulonephritis with necrotizing and crescent formation associated with rheumatoid arthritis [86].…”
Section: Emerging and Less Common Therapiesmentioning
confidence: 98%
“…Przeprowadzona została II faza badań klinicznych nad CCX168 (nazwa handlowa Avacopan) w AAV (https://clinicaltrials.gov, identyfikator badania: NCT01363388). Wstępne doniesienia wskazywały, że stosowanie CCX168 w połączeniu z cyklofosfamidem jest co najmniej równie skuteczne co cyklofosfamid w połączeniu z wysokimi dawkami sterydów u pacjentów z AAV [52]. Najnowsze doniesienia na tym etapie, zaprezentowane podczas kongresu ERA-EDTA w Wiedniu (53rd ERA-EDTA Congress, 2016), potwierdzają bezpieczeństwo i skuteczność CCX168 stosowanego w połączeniu z rytuksymabem lub cyklofosfamidem zamiast standardowo stosowanych wysokich dawek sterydów [53].…”
Section: Znaczenie Netozy I Obecności Zewnątrzkomórkowych Sieci Neutrunclassified